1999
DOI: 10.1016/s1097-2765(00)80366-4
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Sec14p Deficient in Phosphatidylinositol Transfer Activity Is Functional In Vivo

Abstract: Yeast phosphatidylinositol transfer protein (Sec14p) is essential for Golgi secretory function. It is widely accepted, though unproven, that phosphatidylinositol transfer between membranes represents the physiological activity of phosphatidylinositol transfer proteins (PITPs). We report that Sec14pK66,239A is inactivated for phosphatidylinositol, but not phosphatidylcholine (PC), transfer activity. As expected, Sec14pK66,239A fails to meet established criteria for a PITP in vitro and fails to stimulate phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 39 publications
6
152
0
Order By: Relevance
“…In vegetative sec14(K66A K239A) cells, the synthesis of PtdIns(4)P is reduced (Phillips et al, 1999), and overexpression of the PtdIns 4-kinase Pik1p suppresses the growth defect of sec14-1 cells at semirestrictive temperature (Hama et al, 1999). Similarly, we found that overexpression of PIK1 could restore the sporulation of sec14-1 diploids to near wild-type frequency, and suppression of the meiotic defect was dependent on Spo14p (Table 2, lines 19 -20).…”
Section: Suppression Of Sec14 Sporulation Defect By Overexpression Ofmentioning
confidence: 58%
See 3 more Smart Citations
“…In vegetative sec14(K66A K239A) cells, the synthesis of PtdIns(4)P is reduced (Phillips et al, 1999), and overexpression of the PtdIns 4-kinase Pik1p suppresses the growth defect of sec14-1 cells at semirestrictive temperature (Hama et al, 1999). Similarly, we found that overexpression of PIK1 could restore the sporulation of sec14-1 diploids to near wild-type frequency, and suppression of the meiotic defect was dependent on Spo14p (Table 2, lines 19 -20).…”
Section: Suppression Of Sec14 Sporulation Defect By Overexpression Ofmentioning
confidence: 58%
“…Thus, the reduction in Spo14p activity observed in sec14-1 cells could be due to the loss of Sec14p-dependent transport of the substrate, PtdCho, to the cellular compartment(s) where Spo14p functions, to loss of Sec14p-dependent transport of PtdIns and the consequent failure to synthesize the PLD activator PtdIns(4,5)P 2 , or both. To explore the relative contributions of PtdIns and PtdCho binding/transport by Sec14p, we took advantage of a mutant, sec14(K66A K239A), that retains the ability to bind and transport PtdCho but is specifically defective in PtdIns binding and transport (Phillips et al, 1999). This mutant supports the essential function of Sec14p for growth and secretion in vegetative cells (Phillips et al, 1999).…”
Section: Ptdins Binding/transport Activity Of Sec14p Is Required For mentioning
confidence: 98%
See 2 more Smart Citations
“…Analysis of bypass mutants has led to the suggestion that Sec14p is required for maintenance of a critical pool of diacylglycerol [21,22]. Moreover, Sec14p can also fa-cilitate PtdIns4P production in i o [22,23] ; this lipid might also be a critical requirement in protein secretion. In another yeast, Yarrowia lipolytica, SEC14 is not an essential gene and is required only for differentiation from yeast to a mycelial growth form [24].…”
Section: Introductionmentioning
confidence: 99%